2021
DOI: 10.1002/1348-9585.12248
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors affecting Infant at Work policies and programs in university settings

Abstract: Objectives This study identifies the ecological (ie, policy, environment, intrapersonal, and interpersonal) factors affecting the implementation of an Infant at Work program in a university setting. Methods Data were collected among faculty, staff, and graduate students at a large Midwestern university from February to July 2020 via focus group (FG) discussions with university employees (n = 22) and semistructured interviews with university administrators (n = 10). We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…They also do not know that breastfeeding can be done in the workplace. 18 Studies in Ghana and Jakarta reported that working mothers with good knowledge are more likely to breastfeed their babies exclusively. 19,20 The study by Jara-Palacios et al showed that primigravida mothers are more at risk of exclusive breastfeeding for less than six months due to lack of experience and knowledge about the benefits of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…They also do not know that breastfeeding can be done in the workplace. 18 Studies in Ghana and Jakarta reported that working mothers with good knowledge are more likely to breastfeed their babies exclusively. 19,20 The study by Jara-Palacios et al showed that primigravida mothers are more at risk of exclusive breastfeeding for less than six months due to lack of experience and knowledge about the benefits of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%